Briefkaart uit serie van acht waarvan de opbrengst bestemd is voor aktiviteiten van de vredesbeweging - Opland (1981)
Briefkaart uit serie van acht waarvan de opbrengst bestemd is voor aktiviteiten van de vredesbeweging.